Implementation of the Authority of the Public Prosecutor in Resolving Corruption Cases Based on Restorative Justice (Case Study at the Semarang District Attorney's Office) - Supriyadi, Ujang; Gunarto, Gunarto (UNISSULA Semarang, 2025)
Abstract. This study aims to determine, examine, and analyze the implementation of the authority of the public prosecutor in resolving corruption crimes based on restorative justice at the Semarang District Attorney's Office, obstacles and solutions for the public prosecutor in resolving corruption crimes based on restorative justice at the Semarang District Attorney's Office and the concept of implementing the authority of the public prosecutor in resolving corruption crimes based on restorative justice in the future. The approach method used in this study is Sociological juridical. The specifications of this study are descriptive analytical. The data source used is primary data. While secondary data is obtained from literature study research consisting of primary legal materials, secondary legal materials, and testier legal materials. Based on the results of the study, it can be concluded that the implementation of the authority of the public prosecutor in resolving corruption crimes based on restorative justice at the Semarang District Attorney's Office is in exercising the authority as a public prosecutor to resolve corruption cases based on the Criminal Code. Obstacles and solutions for public prosecutors in resolving corruption crimes based on restorative justice at the Semarang District Attorney's Office are that not all corruption cases meet the requirements for restorative justice, there are no specific, firm rules. However, in facing these obstacles, the Semarang District Attorney's Office uses solutions such as compiling special regulations, increasing prosecutors' understanding of the Restorative Justice mechanism specifically in serious crimes. The concept of implementing the authority of the public prosecutor in resolving corruption crimes based on restorative justice in the future is by enforcing the law on corruption crimes fairly and just substantively, not just procedural formalities.